2019
DOI: 10.26444/aaem/102624
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive properties of young green barley extracts in in vitro model of colon cancer

Abstract: Introduction and objective. Young green barley is the most valuable source of nutrients and bioactive substances. It has a broad spectrum of health-promoting properties such as antioxidant, anti-inflammatory, hypoglycaemic, anti-depressant, anti-atherosclerotic and anticancer. The presented study is an attempt to extend this knowledge with particular emphasis on the possibility of using green barley in colon cancer prevention. Materials and method. Extracts were prepared on the basis of two commercial products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
4
4
0
Order By: Relevance
“…On the contrary, as expected, 10 μM 5-fluorouracil and 10 μM cis-platin decreased metabolic activity of CCD841 CoTr cells by 23.2% and 10.6%, respectively. Data obtained from YB correspond with earlier studies by the authors which demonstrated that juice and young green barley water extract had low cytotoxicity on human colon epithelial cell lines CCD841 CoTr and CCD841 CoN [9,10], nor did they impact on the proliferation of CCD841 CoN cells [9].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…On the contrary, as expected, 10 μM 5-fluorouracil and 10 μM cis-platin decreased metabolic activity of CCD841 CoTr cells by 23.2% and 10.6%, respectively. Data obtained from YB correspond with earlier studies by the authors which demonstrated that juice and young green barley water extract had low cytotoxicity on human colon epithelial cell lines CCD841 CoTr and CCD841 CoN [9,10], nor did they impact on the proliferation of CCD841 CoN cells [9].…”
Section: Resultssupporting
confidence: 86%
“…Changes in the morphology and growth pattern of HT-29 cells induced by YB extracts were similar with alterations observed by Kawka et al during examination of previously mentioned young green barley extracts YGB GW and YGB INT [9]. Furthermore, suggestions of necrosis induction in HT-29 cells treated with YB is supported by results obtained by Czerwonka et al, who proved this type of death in human colon cancer cells exposed to water extract of young green barley (HWE) [10].…”
Section: Induction Of Morphological Changes On Human Colon Epithelialsupporting
confidence: 85%
See 3 more Smart Citations